The Technology Development in the Education Field - Arridho, M.; Sari, Novita; Ilham, Rafil Wal; Amini, Waslia (Al'Adzkiya Journal, 2023)
The development of technology that is increasingly rapid today has led to the development of the world of education and one of them is the development of learning media. Learning media is the most important factor that supports success in learning. Learning technology is an application or media that has been designed in a modern way and used as theory and practice in learning, as a learning resource. Currently, the technology widely used in the world of education is information technology. However, technological developments also have negative and positive impacts. The positive impacts include such as adding information, making material delivery more interesting, and increasing interest in learning. Meanwhile, the negative impacts of technology are causing students to be lazy to study, the occurrence of immoral violations, the emergence of deviant behaviour, and the misuse of technology to commit criminal acts.The purpose of this study is to find answers to the problems above. The development of technology in the field of education is rapidly advanced especially in learning media.From the results of this study, the authors can conclude that technological developments, especially in the world of education, are also stated to be beneficial so that students do not get bored while learning, especially nowadays which is increasingly sophisticated using information technology. The benefits of technological developments are the existence of new learning methods, facilitating access for learning, both remotely and at close range, searching for information using the web, and improve learning abilities. Communication as an educational medium is carried out using communication media such as telephone, computer, internet, e-mail and so on. Interaction between teachers and students is not only conducted face-to-face but is also carried out using these media.